2015
DOI: 10.1111/jnc.13282
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal acid‐induced [Zn2+]i elevations calibrated using the low‐affinity ratiometric probe FuraZin‐1

Abstract: The experiments were carried out on primary cultures of murine cortical neurons from cryopreserved preparations obtained from embryonic-day-16 fetuses. To calibrate acid-induced intracelluar [Zn2+] ([Zn2+]i) elevations, a low affinity (Kd = 39 μM at pH 6.1) ratiometric Zn2+ probe, FuraZin-1, was used. A pHi drop from 7.2 to 6.1 caused [Zn2+]i elevations reaching 2 μM; when the thiol-reactive agent N-ethylmaleimide (NEM) was subsequently applied, [Zn2+]i increased further to 5.6 μM; analogous acid- and NEM-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Our findings showed that cultured primary neurons from all three regions studied had similar total zinc contents (since each neuron had similar soma volumes) and showed a uniform subcellular distribution of zinc. This finding is consistent with the idea that the amount of free Zn 2+ accumulated in organelles (like that seen in the cytosol [ 27 , 29 ]) is negligible when compared with the amount coordinated via thiol and other groups and bound to proteins [ 19 , 29 ] giving zinc a fairly uniform average concentration throughout the cytoplasm and nucleus of individual somata.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings showed that cultured primary neurons from all three regions studied had similar total zinc contents (since each neuron had similar soma volumes) and showed a uniform subcellular distribution of zinc. This finding is consistent with the idea that the amount of free Zn 2+ accumulated in organelles (like that seen in the cytosol [ 27 , 29 ]) is negligible when compared with the amount coordinated via thiol and other groups and bound to proteins [ 19 , 29 ] giving zinc a fairly uniform average concentration throughout the cytoplasm and nucleus of individual somata.…”
Section: Discussionsupporting
confidence: 89%
“…To culture the neurons, neurobasal medium supplemented with 2% B27 and 2 mM glutamine was used. The cells were cultured in a humidified incubator maintained at 37°C and 5% O 2 , 5% CO 2 and 90% N 2 atmosphere [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%